2022
DOI: 10.3389/fpsyg.2022.927562
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Run Influence of Education on Subjective Well-Being: The Role of Information and Communication Technology in China

Abstract: Subjective well-being is defined as how happy and satisfied a person is in his life. To date, among the significant determinants of subjective well-being, national income is considered an important one. However, not much focus has been paid to other determinants of subjective well-being, such as education and information and communication technologies (ICTs). Therefore, this study aims to investigate the short- and long-run impact of education and ICTs on subjective well-being in China over the period 1996–202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
1
15
0
3
Order By: Relevance
“…Another study in British found a significant correlation between agreeableness and both religious background and frequency of religious service attendance (Furnham and Cheng, 2015). Another study in Germany found that respondents who scored higher on the agreeableness scale had a greater chance of belonging to the ambitious profile than those who scored higher on the moderate scale (Smidt et al, 2015;Wang and Sohail, 2022). With this discussion, we have hypothesized that: H1a: Students' agreeableness personality trait will positively influence their satisfaction with online learning/teaching modes during COVID-19.…”
Section: Agreeablenessmentioning
confidence: 93%
“…Another study in British found a significant correlation between agreeableness and both religious background and frequency of religious service attendance (Furnham and Cheng, 2015). Another study in Germany found that respondents who scored higher on the agreeableness scale had a greater chance of belonging to the ambitious profile than those who scored higher on the moderate scale (Smidt et al, 2015;Wang and Sohail, 2022). With this discussion, we have hypothesized that: H1a: Students' agreeableness personality trait will positively influence their satisfaction with online learning/teaching modes during COVID-19.…”
Section: Agreeablenessmentioning
confidence: 93%
“…A possible explanation is that the more public employees are concerned about investigating and dispelling rumors, the more attention will be paid to the prevention of the epidemic, and the more transparent and accurate the epidemic information will become. In addition, investigating rumors and punishing those propagating those rumors is conducive to eliminating public panic ( 56 , 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the effectiveness of the emergency plan also has a relatively significant impact on the work cognition of public employees. For this, a possible explanation is that the more imperfect the contingency plan is, the more disadvantaged the public employees are when making a rapid prejudgment of the general trend and responding in the event of an outbreak ( 56 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakistan is one of the countries most susceptible to natural calamities. One of the most important environmental problems caused by global climate change is flooding, as Pakistan has experienced over the past 6–7 years ( Webster, 2011 ; Azam and Mariani, 2012 ; Surminski and Oramas-Dorta, 2014 ; Yen et al, 2017 , 2021 ; Sohail et al, 2020 ; Zinda et al, 2021 ; Wang and Sohail, 2022 ). Natural disasters, such as floods, droughts, scorching temperatures, and high rates of pests and disease, have been more frequent and severe in the United States over the previous 10 years ( Smit and Skinner, 2002 ).…”
Section: Introductionmentioning
confidence: 99%